Here Be Dragons: Using Dragons as Models for Phylogenetic Analysis - Cruz, Ronald Allan L (Archīum Ateneo, 2017)
Dragons are a staple of fantasy literature, and various aspects of the creatures (most notably their anatomy) have been explored scientifically across different forms of media. Their distinct anatomical characteristics and the variations therein among the recognized “species” of dragons make the taxa appropriate models for basic phylogenetic analysis in an undergraduate general biology or systematics class. The wyvern, an obviously more primitive, distant cousin of the “true” dragons, is also an appropriate outgroup for these estimations of shared evolutionary history. Separating metallic from chromatic dragons, the generated tree shows relationships among the species that are consistent with their separation in the Dungeons & Dragons games according to alignment, scale color, and religion, three characters that are not used in the analysis. Manual construction of a character matrix and cladogram of dragons followed by repetition of this process via conventional computer software allows the students to track their progress not only in terms of understanding such concepts as choice of character states and parsimony but also in terms of the applicability of said software.